Premotor and Posterior Parietal Cortex Activity is Increased for Slow, as well as Fast Walking Poststroke: An fNIRS Study - Shannon B. Lim; Sue Peters; Chieh-ling Yang; Lara A. Boyd; Teresa Liu-Ambrose; Janice J. Eng (Neural Plasticity)
Background and Purpose. The ability to change gait speeds is important for interacting with the surrounding environment. Gait speed modulation poststroke is often impaired and is related to decreased walking independence after stroke. Assessment of brain activation during walking at different speeds can provide insight into important regions for facilitating gait recovery. The purpose is to determine: (1) the symmetry of brain activation as individuals increase or decrease their gait speed, (2) the activation levels in frontal to parietal brain regions during walking at different speeds, and (3) the relationship between an individual’s stroke impairment or their ability to modulate their gait speed and change in their brain activation. Methods. Twenty individuals in the chronic stage of stroke walked: (1) at their normal pace, (2) slower than normal, and (3) as fast as possible. Functional near-infrared spectroscopy was used to assess bilateral prefrontal, premotor, sensorimotor, and posterior parietal cortices during walking. Results. No significant differences in laterality were observed between walking speeds. The ipsilesional prefrontal cortex was overall more active than the contralesional prefrontal cortex. Premotor and posterior parietal cortex activity were larger during slow and fast walking compared to normal-paced walking with no differences between slow and fast walking. Greater increases in brain activation in the ipsilesional prefrontal cortex during fast compared to normal-paced walking related to greater gait speed modulation. Conclusions. Brain activation is not linearly related to gait speed. Ipsilesional prefrontal cortex, bilateral premotor, and bilateral posterior parietal cortices are important areas for gait speed modulation and could be an area of interest for neurostimulation.